Antiplatelet therapy following ischaemic stroke: continue or change pre-existing therapy? - Mazlan-Kepli, Wardati; MacIsaac, Rachael L.; Walters, Matthew; Bath, Philip M.W.; Dawson, Jesse (SAGE Publications, 2017)
Introduction: Antiplatelet therapy is routinely prescribed early after ischaemic stroke. Many patients will already be taking antiplatelet therapy and it is unknown whether these patients should continue the same antiplatelet treatment or switch to a different regimen. Methods:We selected patients with ischaemic stroke from the Virtual International Stroke Trials Archive database who were prescribed antiplatelets both before and after their stroke and who had detailed records of adverse events after stroke. We compared patients who changed to a new antiplatelet regimen after their stroke to those who continued the same regimen. The primary outcome was recurrent ischaemic stroke within 90 days after their index stroke and the secondary outcome was intracranial haemorrhage (ICH) or extracranial haemorrhage (ECH). We used logistic regression analysis and adjusted for age and baseline NIHSS. Results: A total of 1129 participants were included. Of these, 538 subjects changed antiplatelet regimen post stroke and 591 continued the same regimen. A recurrent ischaemic event occurred in 4.1% of subjects who changed regimen and 4.3% who continued unchanged (adjusted OR¼0.93; 95% CI 0.54–1.75, p¼0.929). The incidence of ICH and ECH within the first 90 days was similar in both groups (2.4% vs. 2.6% (adjusted OR¼1.02; 95% CI 0.48–2.18, p¼0.955) and 4.7% vs. 2.9% (adjusted OR¼1.82; 95% CI 0.96–3.43, p¼0.065), respectively). Discussion: The analysis was performed using a non-randomised registry data. Conclusion: In patients who suffer ischaemic stroke whilst taking antiplatelets, a change in antiplatelet regimen was not associated with an altered risk of early recurrent ischaemic stroke rate or bleeding. However, the results must be interpreted in view of the low event rates.